Two-Sided Approximation of Solutions of Boundary-Value Problems - Mentynskyi, S. M.; Shuvar, B. A. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We propose a general scheme for the two-sided approximation of solutions of boundary-value problems for ordinary differential equations. This scheme involves a number of known and new two-sided methods. In our investigation, we use constructions of the Samoilenko numerical-analytic method together with the procedure of the construction of two-sided methods proposed by Kurpel’ and Shuvar.